1999
DOI: 10.1017/s002211209900511x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigations of oblique boundary layer transition

Abstract: A transition scenario initiated by two oblique waves is studied in an incompressible boundary layer. Hot-wire measurements and flow visualizations from the first boundary layer experiment on this scenario are reported. The experimental results are compared with spatial direct numerical simulations and good qualitative agreement is found. Also, quantitative agreement is found when the experimental device for disturbance generation is closely modelled in the simulations and pressure gradient effects taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
46
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 41 publications
15
46
1
Order By: Relevance
“…These spikes are associated to ring-like vortices that separate from the tips of the large -vortices. Similar structures have also been found in the late stages of transition in boundary layers, either in the K-, N-or O-regimes of breakdown (see Berlin, Wiegel & Henningson 1999). These observations indicate that a considerable degree of similarity exists in the late stage of transition in a pipe and in a boundary layer.…”
Section: Introductionsupporting
confidence: 75%
“…These spikes are associated to ring-like vortices that separate from the tips of the large -vortices. Similar structures have also been found in the late stages of transition in boundary layers, either in the K-, N-or O-regimes of breakdown (see Berlin, Wiegel & Henningson 1999). These observations indicate that a considerable degree of similarity exists in the late stage of transition in a pipe and in a boundary layer.…”
Section: Introductionsupporting
confidence: 75%
“…The validation of the DNS results for both K-and H-type transitions is corroborated by recovering the aligned arrangement of the Λ vortices for the K-type transition (see figure 15a) and the staggered arrangement for the H-type transition (see figure 15b), as experimentally observed by Berlin, Wiegel & Henningson (1999) for the flat plate boundary layer. Figure 16 shows the evolution of the skin-friction coefficient versus Re δ * for two different normalized height scales.…”
Section: Effect Of Smooth Forward-facing Steps On K-and H-type Transisupporting
confidence: 74%
“…We label these modes using the notation (ω, β) (Berlin et al 1999), where ω and β are, respectively, the frequency and spanwise wavenumber, each normalized by the corresponding fundamental frequency/wavenumber. It has been observed that the K-type transition scenario has its main initial energy in the (1, 0) mode.…”
Section: Effect Of Smooth Forward-facing Steps On K-and H-type Transimentioning
confidence: 99%
“…For example, the development of structures and hairpin vortices was also observed in the late stage of oblique transition (Berlin, Wiegel & Henningson 1999). In this scenario, transition is induced by exciting oblique modes at the inflow, which grow and generate new modes through triad interactions.…”
Section: Comparison With Other Transition Scenariosmentioning
confidence: 99%